2018
DOI: 10.3892/etm.2018.6933
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects different diameters of Tussah silk fibroin nanofibers on olfactory ensheathing cells

Abstract: Transplantation of olfactory ensheathing cells (OECs) has potential for treating spinal cord and brain injury. However, they are void of an extracellular matrix to support cell growth and migration. Engineering of tissue to mimic the extracellular matrix is a potential solution for neural repair. Tussah silk fibroin (TSF) has good biocompatibility and an Arg-Gly-Asp tripeptide sequence. A small number of studies have assessed the effect of the diameter of TSF nanofibers on cell adhesion, growth and migration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Similar to SCs, they can enhance the microenvironment after nerve injury via secretion of neurotrophic factors including brain derived neurotrophic factor, glial derived neurotrophic factor, and nerve growth factor [65,66], as well as extracellular matrix molecules, which together can indirectly activate endogenous SCs [60,[67][68][69]. Compared to SCs, OECs express higher levels of macrophage migration inhibitory factor (MIF), which prevents the infiltration of macrophages into the injury site and thus OECs can modulate the inflammatory response [65,66,70].…”
Section: Incorporated Cellsmentioning
confidence: 99%
“…Similar to SCs, they can enhance the microenvironment after nerve injury via secretion of neurotrophic factors including brain derived neurotrophic factor, glial derived neurotrophic factor, and nerve growth factor [65,66], as well as extracellular matrix molecules, which together can indirectly activate endogenous SCs [60,[67][68][69]. Compared to SCs, OECs express higher levels of macrophage migration inhibitory factor (MIF), which prevents the infiltration of macrophages into the injury site and thus OECs can modulate the inflammatory response [65,66,70].…”
Section: Incorporated Cellsmentioning
confidence: 99%
“…Results indicated that the diameter of the fibers played an important role in guiding cell adhesion, growth, and migration in vitro . In similar lines, culturing of nonmulberry silk nanofibrous mats (tasar silk) with OECs also displayed greater OEC adhesion, growth, and migration on 400 nm diameter of nanofibers (Figure I and II) . On the other hand, structural resemblance of biomineralized nanosilk fibroin films seeded with bone marrow stromal cells to the natural bone has been successfully exploited to induce spinal fusion in rat models .…”
Section: Application Of Silk-based Nanomaterials For 3d Tissue Engine...mentioning
confidence: 91%
“…In similar lines, culturing of nonmulberry silk nanofibrous mats (tasar silk) with OECs also displayed greater OEC adhesion, growth, and migration on 400 nm diameter of nanofibers (Figure 4I and II). 132 On the other hand, structural resemblance of biomineralized nanosilk fibroin films seeded with bone marrow stromal cells to the natural bone has been successfully exploited to induce spinal fusion in rat models. 133 Although the bone volume, relative strength and stiffness, and the bone fusion rate of the cell seeded films were slightly less than those of the autograft, no significant difference was documented.…”
Section: Application Of Silk-based Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation